Gambaran Pengetahuan Dan Motivasi Terkait Pencegahan Human Immunodeficiency Virus / Aquired Immuno Deficiency Syndrome Pada Siswa Sekolah Menengah Atas Dwijendra Denpasar - Ni Putu Dyah Yadnya Swari Widjaya Puja; Ni Komang Yuni Rahyani; Gusti Ayu Marhaeni (Poltekkes Kemenkes Denpasar, 2019)
Adolescence is a group at risk of transmition in Human Immunodeficiency Virus/Aquired Immuno Deficiency Syndrome. This study aims to find out the description of knowledge and motivation in regards to prevention of HIV/AIDS among students of Dwijendra Senior High School Denpasar. This study is a descriptive design of study with cross-sectional approach. This study was conducted from April to May 2019, where 106 respondents were taken as samples by applying purposive sampling technique. The data were collected by using self-reported questionnaire. The result shows that almost 44.3% respondents have high knowledges and high motivations, and respondents who have well knowledges and less motivations were 24,5%. Respondents who have less knowledges and high motivations are 13,2%, and respondents who have less knowledges and low motivations are 18%. Efforts to maintain students’ knowledges and motivations in regards to preventing Human Immunodeficiency Virus/Aquired Immuno Deficiency Syndrome, health workers must to give counseling about the prevention of Human Immunodeficiency Virus/Aquired Immuno Deficiency Syndrome with friendly approach.